If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation.6x − y = 14x − 3y = −11 4(−6x + 1) − 3y = −11 4(6x + 1) − 3y = −11 4x − 3(6x − 1) = −11 4x − 3(−6x − 1) = −11

Accepted Solution

Answer:Equation is  4x-6(6x-1) = -11 Step-by-step explanation:The set of equations given are                           6x-y=1 4x-3y=-11 A pair of linear equations in two variables x and y is given in the set of equations. If there are two variables we require two equations to find the value of variables. Substitution is one among the methods used to solve pair of linear equations in two variables. Here we have to determine the value of y from the first equation and then substitute it in the second equation. 6x-y=1 y=6x-1 Substituting this value in second equation 4x-6y=-11 we get 4x-6(6x-1) = -11